A [Mn18] wheel-of-wheels. Issue 34 (26th March 2021) - Coletta, Marco; Tziotzi, Thomais G.; Gray, Mark; Nichol, Gary S.; Singh, Mukesh K.; Milios, Constantinos J.; Brechin, Euan K.
Abstract : A [Mn18 ] wheel of wheels is constructed from a simple reaction incorporating a triazatriol ligand. Abstract : A [Mn18 ] wheel of wheels is obtained from the reaction of MnBr2 ·4H2 O and LH3 in MeOH. The metallic skeleton reveals two asymmetric [Mn III 6 Mn II 2 ] square wheels connected into a larger wheel via two Mn II ions. Magnetic susceptibility and magnetisation data reveal competing exchange interactions, supported by computational studies.